If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(2 + -4b) = 21 3 + (2 * -1 + -4b * -1) = 21 3 + (-2 + 4b) = 21 Combine like terms: 3 + -2 = 1 1 + 4b = 21 Solving 1 + 4b = 21 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4b = 21 + -1 Combine like terms: 1 + -1 = 0 0 + 4b = 21 + -1 4b = 21 + -1 Combine like terms: 21 + -1 = 20 4b = 20 Divide each side by '4'. b = 5 Simplifying b = 5
| (3y+3)(y^2+3y-4)= | | 5x+6+4x=60 | | (15xy^2)/6xy | | 3y+6y+7=25 | | 18-2g=5g | | 90-47=43 | | 10r+6r-11r=5 | | 4w=128 | | -48-12=n | | 8w-7w=3 | | 9(x+5)=50 | | 16r-13r=18 | | 3.5x+11=25 | | 6d-d=10 | | 7m-5=10m+13 | | y^2-3y-44=10 | | 45-3y-5z+3y+5z=45 | | 6x+2+8=180 | | 0.5x^2+9=4.5x | | 8x^2-32x+28=0 | | 2/3÷90 | | -.5v=.9 | | 10t+3=73 | | 4.5/x=2 | | X-45=70 | | y-2x+5=3 | | 5k-8/4=4 | | 8(2x-2)+x=-6+7x | | 1+3x+(5x-5)=145 | | 8-4a-5=5(a-3) | | 20=3z | | 6x-5+2x+5=90 |